A Vessel-Preserving Surgical Hip Dislocation Through a Modified Posterior Approach: Assessment of Femoral Head Vascularity Using Gadolinium-Enhanced MRI. (16th March 2016) - Sculco, Peter K.; Lazaro, Lionel E.; Su, Edwin P.; Klinger, Craig E.; Dyke, Jonathan P.; Helfet, David L.; Lorich, Dean G.
Abstract : Background: Surgical hip dislocation allows circumferential access to the femoral head and acetabulum and is utilized in the treatment of intra-articular hip disorders. Surgical hip dislocation is currently performed with a trochanteric osteotomy that reliably preserves the femoral head arterial supply; however, trochanteric nonunion or painful hardware requiring removal may occur. In a cadaveric model, using gadolinium-enhanced magnetic resonance imaging (MRI) and gross dissection, we evaluated whether modifications to the posterior approach preserve the femoral head arterial supply after a posterior surgical hip dislocation. Methods: In eight fresh-frozen pelvic specimens, a surgical hip dislocation was performed through the posterolateral approach with modifications in the tenotomy of the short external rotators and a capsulotomy designed to preserve the medial femoral circumflex artery (MFCA). Modifications included tenotomies of the quadratus femoris, conjoined tendon of the short external rotators, and obturator externus made 2.5 cm medial to their insertion on the greater trochanter and a T-type capsulotomy originating below the cut edge of the obturator externus tendon and continuing circumferentially along the acetabular rim. After hip dislocation, the MFCA was cannulated and MRI scans were acquired before and after gadolinium enhancement for evaluation of femoral head perfusion, with the contralateral hip, which was left intact, used as a control. Anatomic gross dissection was performed after the injection of polyurethane in the MFCA and confirmed MFCA vessel integrity. Results: Quantitative MRI showed that the operatively treated hip retained a mean perfusion (and standard deviation) of 95.6% ± 9.7% in the femoral head and 94.7% ± 21.5% in the femoral head-neck junction compared with the control hip (p = 0.66 and p = 0.85, respectively). Dissection after polyurethane injection confirmed that the superior retinacular and inferior retinacular arteries entering the femoral head were intact in all specimens. Conclusions: In a cadaveric model using gadolinium-enhanced MRI, we found that standardized modifications to the posterior approach, specifically with regard to the location of the short external rotator tenotomy and capsulotomy, successfully preserved the femoral head arterial supply after posterior surgical hip dislocation. Clinical Relevance: While further research is necessary before these modifications can be recommended for widespread clinical use, the results of this study suggest the extracapsular vascular anatomy can be safely preserved during posterior surgical hip dislocation.